Kelengkapan Pengisian Rekam Medis Elektronik Pasien di Poli Umum Puskesmas Surabaya Timur - Masyfufah, Lilis; Listiawan, Nadhila; Yulianita, Novi Eka; Wahyuni, Titin; Sutha, Diah Wijayanti; Pribadi, Maylina Surya Wirawati (Akademi Perekam dan Informasi Kesehatan Imelda, 2024)
The digital transformation of health is one proof of technological developments in health services. The implementation of health digitalization in the Surabaya City environment has started on November 10 2014 and in 2020 it will be ready to transform into an Electronic Health Record (EHR). The implementation of EHR began with the implementation of RME at Surabaya City Health Centers since March 2022. However, RME implementation is still not optimal, so research needs to be carried out on the completeness of RME at East Surabaya Regional Health Centers. This research method uses a type of quantitative research that collects data in the form of numbers using an observational approach. The population used is RME patients at Community Health Centers in the East Surabaya Region, namely Menur Health Center and Keputih Health Center, while the research sample will be taken using the Cochran Formula. The results of the identified data will be processed using Microsoft Excel for quantitative analysis and will be presented in table form to describe the object. The results of the research show that incomplete filling in of patients' RME at the East Surabaya Community Health Center General Polyclinic is found in the Identity, Important Reports and Authentication components, while the Documentation component is 100% complete. It can be concluded that the incompleteness of RME filling at the East Surabaya Community Health Center reaches 70%, the data is not complete.